INDONESIAN CRAFT IN THE WORLD TRADE - Timbul Raharjo (Ars: Jurnal Seni Rupa dan Desain, 2018)
Some international craft exhibitions focus on home accessories, gifts, and furniture. The exhibition aim as craft product branding at the national and international market, for example 2016 JIFFINA exhibition. Indonesian craft commodity maintains market share in several export destination countries because Indonesian products offer special characteristics and moreover, Indonesian exporters are enthusiastic in promoting the products in international exhibitions. In Asia level, Canton Fair held in Guangzhou International Convention & Exhibition Center China is one of the biggest programs where a big number of buyers look for products they want to purchase. In Asia, exhibition series peak in Guangzhou in March and in Shanghai in October. These exhibitions are visited by importers from Europe, America, Africa, The Middle East, Australia, etc. They come to buy Asian furniture. Some exhibitions in several countries are intentionally organized within a short time in sequence to grab buyers coming to South East Asian area. It is when the commission products from Indonesian producers, in form of retails or projects. Indonesian stakeholders respond this opportunity by organizing two big exhibitions, namely Indonesia International Furniture Expo (IFEX) in Jakarta and Jogja International Furniture and Craft Fair (JIFFINA) in Yogyakarta